2020
DOI: 10.1007/jhep01(2020)077
|View full text |Cite
|
Sign up to set email alerts
|

Horizon constraints on holographic Green’s functions

Abstract: We explore a new class of general properties of thermal holographic Green's functions that can be deduced from the near-horizon behaviour of classical perturbations in asymptotically anti-de Sitter spacetimes. We show that at negative imaginary Matsubara frequencies and appropriate complex values of the wavenumber the retarded Green's functions of generic operators are not uniquely defined, due to the lack of a unique ingoing solution for the bulk perturbations. From a boundary perspective these 'pole-skipping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
228
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(246 citation statements)
references
References 106 publications
(308 reference statements)
18
228
0
Order By: Relevance
“…It is clear that at these 2 points, the Green's function of the boundary operator, dual to the bulk scalar field Φ, is multi-valued. According to the explanations given in Introduction, based on [37], one concludes that to every Matsubara frequency ω = −i2πT , pole-skipping points of the dual boundary operator correspond. This simply shows that how near horizon dynamics can strictly constrain the Green's function of a generic boundary operator, even beyond the regime of hydrodynamics, namely at frequencies ω ∼ T .…”
Section: Pole-skipping In the Green's Function Of Boundary Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that at these 2 points, the Green's function of the boundary operator, dual to the bulk scalar field Φ, is multi-valued. According to the explanations given in Introduction, based on [37], one concludes that to every Matsubara frequency ω = −i2πT , pole-skipping points of the dual boundary operator correspond. This simply shows that how near horizon dynamics can strictly constrain the Green's function of a generic boundary operator, even beyond the regime of hydrodynamics, namely at frequencies ω ∼ T .…”
Section: Pole-skipping In the Green's Function Of Boundary Operatorsmentioning
confidence: 99%
“…In another way, recently it has been shown that the lack of information to uniquely define a correlation function is not specific to energy density correlation functions at chaos point; Green's functions of generic operators have also the same feature but at negative Matsubara frequencies and some appropriate complex values of wavenumber [37] 7 . The presence of such set of pole-skipping points in the lower half of complex Fourier plane shows that the dispersion relations of collective modes in boundary theory at energy scales ω ∼ T are directly constrained by the near horizon dynamics of bulk fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the physics will remain the same. Here we simply follow the convention used in [17] for the sake of comparison.11 Note that at λGB = 1/4, N 2 GB = 1/2, the shear viscosity vanishes, and the theory exhibits unusual properties in many aspects, such as quasinormal modes and thermodynamics, see [54,59,60] for detailed discussions. Since this value lies far outside of the causality range (4.3), we will not consider it in the following.…”
mentioning
confidence: 99%
“…Of course, the physics will remain the same. Here we simply follow the convention used in [17] for the sake of comparison.…”
mentioning
confidence: 99%